2015
DOI: 10.1155/2015/706276
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Sites ofAedes aegypti: Potential Dengue Vectors in Dire Dawa, East Ethiopia

Abstract: Background and Objectives. Entomological survey was carried out from May-June to September-October 2014 to investigate the presence of dengue vectors in discarded tires and artificial water containers in houses and peridomestic areas. Methods. A cross-sectional immature stage survey was done indoors and outdoors in 301 houses. Mosquito larval sampling was conducted using pipette or dipper depending on container types. Larvae were identified morphologically and larval indices were also calculated. Results. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
129
4
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 23 publications
19
129
4
11
Order By: Relevance
“…Aedes mosquito showed its preference with tires, the positive composition took up to 28%. The results are consistent with that of research papers on breeding sites [17][18][19][20]. The lowest positive jars in house in our results might have relevant with the vector control work in 2013.…”
Section: Discussionsupporting
confidence: 93%
“…Aedes mosquito showed its preference with tires, the positive composition took up to 28%. The results are consistent with that of research papers on breeding sites [17][18][19][20]. The lowest positive jars in house in our results might have relevant with the vector control work in 2013.…”
Section: Discussionsupporting
confidence: 93%
“…The more extensive the reporting, the more accurate the prevalence rates. Other factors that contribute are reduced public health awareness, population density, infecting DENV strain, urban planning activities, topography, water storage practices, change of lifestyle, apathy and heightened medical seeking behaviour [20][21][22][23]. Variation in the number of laboratory tests conducted can also influence this was well as more tests conducted will results in more cases detected.…”
Section: Discussionmentioning
confidence: 99%
“…Drums were also often used for water storage; however, most were found negative for mosquito larvae. One study in Dire Dawa, Ethiopia, found that artificial breeding sites (in particular tyres and plastic drums) were the primary source of vectors (37,38), however there sampling was conducted in an urban area. Various studies found differing types of containers responsible for Aedes spp.…”
Section: Discussionmentioning
confidence: 99%